2021
DOI: 10.3389/fphys.2021.683669
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina platensis Alleviated the Hemotoxicity, Oxidative Damage and Histopathological Alterations of Hydroxychloroquine in Catfish (Clarias gariepinus)

Abstract: The current study aims at evaluating the toxicity of hydroxychloroquine (HCQ) as a pharmaceutical residue in catfish (Clarias gariepinus) and the protective role of Spirulina platensis (SP). Four groups were used in this study: (1) a control group, (2) a group exposed to 3.16 mg/l of HCQ, (3) a group exposed to 3.16 mg/l of HCQ + 10 mg/l of SP, and (4) a group exposed to 3.16 mg/l of HCQ + 20 mg/l of SP for 15 days of exposure. The HCQ-treated group showed a significant decline in the hematological indices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
8
12
0
Order By: Relevance
“…Liver tissue in the exposed fish showed deformation of hepatocytes, including hepatocytes collected in a rosette shape around the blood sinusoids, necrotic areas of degenerated hepatocytes, many pyknotic nuclei, dilated and congested blood sinusoids, hemorrhage in the central veins, shrunken and fatty degeneration of hepatocytes, and severe depletion of polysaccharide contents. Similar alterations were reported in common carp exposed to lead acetate (Mustafa et al, 2017) and PE-MPs (Hamed et al, 2022), in catfish exposed to MPs (Sayed et al, 2022) and 4-NP (Sayed and Soliman, 2018), in zebrafish as combined effects of MPs and chemical contaminants (Rainieri et al, 2018), as well as other types of fish exposed to different toxins (Figueiredo-Fernandes et al, 2007;da Costa et al, 2016;Espinosa et al, 2019;Soliman et al, 2019;da Costa Araujo et al, 2020;Naguib et al, 2020;Sayed et al, 2021). In addition to glycogen and lipid deposition, the observed hepatic vacuolations may reflect abnormal liver metabolic processes (Myers et al, 1987).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Liver tissue in the exposed fish showed deformation of hepatocytes, including hepatocytes collected in a rosette shape around the blood sinusoids, necrotic areas of degenerated hepatocytes, many pyknotic nuclei, dilated and congested blood sinusoids, hemorrhage in the central veins, shrunken and fatty degeneration of hepatocytes, and severe depletion of polysaccharide contents. Similar alterations were reported in common carp exposed to lead acetate (Mustafa et al, 2017) and PE-MPs (Hamed et al, 2022), in catfish exposed to MPs (Sayed et al, 2022) and 4-NP (Sayed and Soliman, 2018), in zebrafish as combined effects of MPs and chemical contaminants (Rainieri et al, 2018), as well as other types of fish exposed to different toxins (Figueiredo-Fernandes et al, 2007;da Costa et al, 2016;Espinosa et al, 2019;Soliman et al, 2019;da Costa Araujo et al, 2020;Naguib et al, 2020;Sayed et al, 2021). In addition to glycogen and lipid deposition, the observed hepatic vacuolations may reflect abnormal liver metabolic processes (Myers et al, 1987).…”
Section: Discussionsupporting
confidence: 63%
“…Several contaminants have been shown to alter some tissues in different types of fish (Sayed and Soliman, 2018;Sayed et al, 2021;Hamed et al, 2022). In this study, the liver, gills, and brain of juvenile carp showed some alterations after continuous exposure to 10 mg/L PE-MPs, 10 mg/L PE-MPs + 200 µg/L 4-NP, and 200 µg/L 4-NP for two weeks, followed by two weeks of recovery.…”
Section: Discussionmentioning
confidence: 63%
“…Higher enzyme levels are detected from the blood samples test, such as lactic dehydrogenase, AST, ALT, creatine kinase, and alkaline phosphatase, which correspond to damage to cell membranes (Banaee 2013). Such results are in agreement with other reported findings (Gill et al, 1992;Kazlauskienė and Stasiunaitė 1999;Monteiro et al, 2005;Heydarnejad et al, 2013;Pretto et al, 2014;Abdel-Khalek et al, 2015;Hamed et al, 2019a;Hamed et al, 2019b;Osman et al, 2019;Sayed et al, 2019;Soliman et al, 2019;Sayed et al, 2021a;Sayed et al, 2021b;Soliman et al, 2021;Hamed et al, 2022;Sayed et al, 2022). The variation in glucose levels is related to the glycogenolysis and gluconeogenesis processes occurring in the liver and kidney (Oner et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Aquatic organisms were tested for various environmental stress effects using antioxidant biomarkers (Sayed et al, 2021). In the present study, the activities of SOD and TAC were significantly decreased in the two groups of exposure, these results agree with Hamed et al (2020) as they reported a decrease in total antioxidant capacity (TAC) in Nile Tilapia after exposure to microplastic and with disagreement with Hoseini et al (2022) as they noted a significant increase in SOD levels in common carp as a result of stress, whereas malondialdehyde (MDA) concentration showed a significant increase in the low dose and a significant increase in the high dose dexamethasone exposed group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the levels of antioxidant enzymes were decreased compared with the control. Sayed et al (2021) reported that there was a depletion of antioxidant enzymes in catfish (Clarias gariepinus) after exposure to hydroxychloroquine. In contrast, José et al (1997) observed an increase in catalase and superoxide dismutase enzymes in the adult rat lung after dexamethasone injection.…”
Section: Discussionmentioning
confidence: 99%